2011
DOI: 10.1007/s00276-011-0844-4
|View full text |Cite
|
Sign up to set email alerts
|

Computer-assisted three-dimensional reconstruction of the fetal pancreas including the supplying arteries according to immunohistochemistry of pancreatic polypeptide

Abstract: PurposeComputer-assisted three-dimensional reconstruction of the fetal human pancreas was prepared to reconsider topographical relation between the dorsal/ventral anlagen and the vascular supply.MethodsTissue sections from the upper abdominal viscera of three fetuses were examined. Sections were immunohistochemically stained to determine pancreatic polypeptide expression, a marker of the ventral pancreas.ResultsThe immunohistochemical findings were used to create three-dimensional computer-assisted reconstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…As a result, the intrapancreatic bile duct runs between the dorsal and ventral pancreas, neither inside the dorsal pancreas nor the ventral pancreas. This configuration is confirmed in human fetal pancreas as well [ 9 ]. Also, the intrapancreatic bile duct is covered by the pancreatic lingula [ 8 ], which derives from the ventral pancreas.…”
Section: Discussionsupporting
confidence: 56%
“…As a result, the intrapancreatic bile duct runs between the dorsal and ventral pancreas, neither inside the dorsal pancreas nor the ventral pancreas. This configuration is confirmed in human fetal pancreas as well [ 9 ]. Also, the intrapancreatic bile duct is covered by the pancreatic lingula [ 8 ], which derives from the ventral pancreas.…”
Section: Discussionsupporting
confidence: 56%
“…Due to the thick portal vein, we originally regarded the portal vein bifurcation as the most superiorly located structure in the hilar vessels and ducts. Indeed, we previously showed that the fetal topographical anatomy near and on the pancreatic head differ considerably from that in adults (Jin et al,2010; Yu et al,2011). In particular, we found that the portal vein and the hepatic artery arising from the superior mesenteric artery were on the superior side of the pancreatic head.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these specimens may have contained anomalies at or close to the GB. However, using our previous experience (Hwang et al,2010; Jin et al,2010; Yu et al,2011) and critical views of hepatic duct variation (Fig. 1; see the Introduction), we carefully determined whether any morphology was common to the specimens.…”
Section: Methodsmentioning
confidence: 99%
“…Fungi are well-known producers of bioactive secondary metabolites, especially short peptides of 30 residues or fewer, with interesting structures and antibiotic properties (Brase et al 2009;Jia et al 2015;Li et al 2017;Wang et al 2017a, b;Yu et al 2012). Herein, we focus on fungal cyclodipeptides known as 2,5-diketopiperazines (DKPs), as well as typical peptides and their analogs, reported since 2000.…”
Section: Introductionmentioning
confidence: 99%